Amelioration of LPS-Induced Inflammation Response in Microglia by AMPK Activation. (16th June 2014) - Chen, Chin-Chen; Lin, Jiun-Tsai; Cheng, Yi-Fang; Kuo, Cheng-Yi; Huang, Chun-Fang; Kao, Shao-Hsuan; Liang, Yao-Jen; Cheng, Ching-Yi; Chen, Han-Min
Abstract : Adenosine 5′-monophosphate-activated protein kinase (AMPK) is a key regulator of cellular energy homeostasis via modulating metabolism of glucose, lipid, and protein. In addition to energy modulation, AMPK has been demonstrated to associate with several important cellular events including inflammation. The results showed that ENERGI-F704 identified from bamboo shoot extract was nontoxic in concentrations up to 80  μ M and dose-dependently induced phosphorylation of AMPK (Thr-172) in microglia BV2 cells. Our findings also showed that the treatment of BV2 with ENERGI-F704 ameliorated the LPS-induced elevation of IL-6 and TNF- α production. In addition, ENERGI-F704 reduced increased production of nitric oxide (NO) and prostaglandin E2 (PGE2) via downregulating the expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase 2 (COX-2), respectively. Moreover, ENERGI-F704 decreased activated nuclear translocation and protein level of NF- κ B. Inhibition of AMPK with compound C restored decreased NF- κ B translocation by ENERGI-F704. In conclusion, ENERGI-F704 exerts inhibitory activity on LPS-induced inflammation through manipulating AMPK signaling and exhibits a potential therapeutic agent for neuroinflammatory disease.